Path Loss Model for Future Terahertz (THz) Wireless Communication Systems: Path Loss Model for Future Terahert z Wireless Communication Systems - Shah, Sabir; Ashraf, Majid; Saeed, Nasir; Jan, Tariqullah; Khalil, Ruhulamin; Babar, M. Inayatullah; Ahmad, Gulzar; Shah, Syed Waqar (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Terahertz (THz) band is visualized to alleviate the capacity limitation and spectrum scarcity of the current wireless communication system. One of the major constraints for the realization of THz wireless communication is the high path loss. Terahertz band wireless communication have a very high molecular absorptions well as molecular noise generated by water vapor in response to attenuation of electromagnetic radiation that have a very high path loss propagation. Besides molecular losses communication in the terahertz spectrum has also spreading losses like reflection and scattering losses. Taking into account all these peculiarities of the terahertz radiation a proposed channel model based on ray approach is designed that accounts for terahertz wave propagation. An equivalent path loss model for terahertz multipath propagation based on ray tracing approach is developed and corroborated with the existing experimental results.